The Mediation Role of Job Satisfaction and Organizational Commitment In The Relationship Between Person-Organization Fit (P-O Fit) and Employee Performance - Tri Prasetyaningrum; Hidajat Hendarsjah (Business Review and Case Studies, 2022)
This study aims to empirically prove the relationship between person-organization (P-O-Fit) on employee performance with job satisfaction and organizational commitment as mediating variables. The research sample was carried out by purposive sampling with 354 respondents, consisting of several regional officials, the Madiun City Government. Testing the research hypothesis used the Baron and Kenny method, with a series of multiple linear regression models. The results uncovered that (1) there was an influence of P-O Fit on job satisfaction of 8.1%. (2) There was an effect of P-O Fit on organizational commitment of 11.7%. (3) There was an influence of job satisfaction on employee performance of 13.2%. (4) There was an effect of organizational commitment on employee performance of 10.6%. However, (5) there was no effect of P-O Fit on employee performance. In addition, (6) there was a mediating effect of job satisfaction on the relationship between P-O Fit and employee performance. (7) There was also a mediating effect of organizational commitment on the relationship between P-O Fit and employee performance.